From policy frontier to policy dilemmas : the United States and Caribbean migration, 1960-1990. - Mitchell, Christopher (1992)
Provides a brief overview of the timing and size of Caribbean migration since 1960. Reviews the making of U.S. immigration policy. Examines current policy stance of the U.S.